2010
DOI: 10.1139/x10-162
|View full text |Cite
|
Sign up to set email alerts
|

Water availability and genetic effects on wood properties of loblolly pine (Pinus taeda)

Abstract: We studied the effect of water availability on basal area growth and wood properties of 11-year-old loblolly pine ( Pinus taeda L.) trees from contrasting Florida (FL) (a mix of half-sib families) and South Carolina coastal plain (SC) (a single, half-sib family) genetic material. Increasing soil water availability via irrigation increased average whole-core specific gravity (SG) and latewood percentage (LW%) by 0.036 and 6.93%, respectively. Irrigation did not affect latewood SG or wood stiffness, but irrigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…In a loblolly pine irrigation-fertilization trial, an improvement in outerwood LW SG was observed following irrigation [90]. Conversely, in another experiment where trees were only irrigated, whole-core SG increased in the irrigated trees, but latewood SG did not change [91]. In both studies, it was found that irrigation enabled LW formation to continue later into the growing season.…”
Section: Irrigationmentioning
confidence: 99%
“…In a loblolly pine irrigation-fertilization trial, an improvement in outerwood LW SG was observed following irrigation [90]. Conversely, in another experiment where trees were only irrigated, whole-core SG increased in the irrigated trees, but latewood SG did not change [91]. In both studies, it was found that irrigation enabled LW formation to continue later into the growing season.…”
Section: Irrigationmentioning
confidence: 99%
“…The derivative method involves fitting a model to the SG profile of each tree (or plot) with ring number as an explanatory variable and taking the first derivative of the fitted function with respect to ring number (Mora et al, 2007;Gonzalez-Benecke et al, 2010). A 4-parameter logistic function was used to explain the change in SG with ring number as presented below …”
Section: Juvenile -Mature Wood Demarcationmentioning
confidence: 99%
“…When there was no moisture limitation, diameter growth continues until late in the season when other factors (temperature or photoperiod) trigger cessation. Gonzalez-Benecke et al (2010) [19] found similar results for loblolly pine and concluded that there was a strong and positive relationship between high soil water availability and gain in ring SG and LW%. During first five growing seasons, competing vegetation cover percent was much larger at the plots without post-planting vegetation control [7], so it can be assumed that in those plots the trees had less soil moisture available due to more competition for water, and thus may have had a shorter latewood growing season due to water limitations.…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, when growing conditions are optimal, EW growth is enhanced and the proportion of LW is reduced. When water availability is not limiting during LW formation, higher SG wood is produced due to extended growing season that produced more LW [19]. Barnett et al (2003) [20] came to the same conclusion; increasing water availability can significantly increase the ratio of LW to EW of temperate-zone conifers by delaying the entry of the cambium into dormancy during cambial growth in mid-to late-summer.…”
Section: Introductionmentioning
confidence: 93%